School Climate Coordinators in Chile: Understanding their Labor Identity - Valenzuela, Jaime (2018)
Addressing school climate and violence in schools requires school management skills. The 2011 School Violence Act in Chile promulgated the mandatory creation of the school climate coordinator (SCC). However, the law did not establish a defined profile, specific functions, or working hours for the SCC, and only recently have school administrators given SCCs more time for this position. This has created a flexible operating framework for the position, which could have implications in terms of the labor identity of the SCCs. This exploratory study employed a qualitative case study. An exploratory focus group was conducted with the school climate committee and three in-depth interviews with the SCC of one municipal school. Content analyses revealed the ambiguity of the SCC figure due to a fragmentation of roles in the areas of pedagogy, administration and school climate, creating a scenario where the roles of teacher, inspector, and SCC are segmented. We discuss how the notion of school climate is separated within the school practice from the dimensions of pedagogy school management, and its possible effects.